STRUKTURA ORGANIZACYJNA ORAZ GŁÓWNE KIERUNKI DZIAŁALNOŚCI NORDYCKIEJ RADY MINISTRÓW - Filipek, Michał Jan (Zeszyty Prawnicze, 2017)
Organizational Structure and Main Activities of the Nordic Council of Ministers Summary The aim of the paper is to present basic information concerning structure and political activity of The Nordic Council of Ministers. The Nordic Council of Ministers was established in 1971 after an attempt at Nordic economic co-operation, the so-called Nordek, which had failed the year before. One of the main goals of the Nordic Council of Ministers was to maintain Nordic co-operation and integration. Denmark, Finland, Iceland, Norway and Sweden have been members of the Nordic Council of Ministers since 1971. The autonomous territories of Greenland, the Faroe Islands and Åland have also increased their representation and position in the Nordic Council of Ministers (the same representation as the member states). The Nordic Council of Ministers has developed contacts with all of the countries in the Baltic Sea Region. Closer co-operation with the Baltic States takes the form of rich co-operation on many levels. The Nordic Council of Ministers is the forum for Nordic governmental co-operation. Issues are prepared and followed up by the various Committees of Senior Officials which consist of civil servants from the member countries. The purpose of inter-governmental and political co-operation in the Nordic Council of Ministers is to work toward joint Nordic solutions that have positive effects for the citizens of Nordic countries.